Discrimination of women on work place - relation to maternity, disability and women’s health - Dobrosavljević-Grujić Ljiljana (Temida, 2006)
A special kind of discrimination of women on work place is that related to their psychophysical condition. Whereas the health condition is often a pretext for discrimination of pregnant women, young mothers, sick and disabled women workers, the mobbing at work is discrimination that may have psychical troubles as a consequence. We present a brief analysis of relevant international and domestic regulations, demonstrating explicitly their breaking on the examples from the work of SOS Hotline for women victims of discrimination at work. The conclusion is that for struggle against the discrimination related to psychophysical condition of workingwomen it is important to fight against breaking the positive legal regulations, as well as working on their improvement. .